Antioxidant Based Functional Drink Formulation as an Alternative Diet Drink for Diabetes and Cholesterol - Dewi, Yuli Kusuma (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2025)
Unhealthy lifestyle in modern era brings public health issues to metabolic disorders that trigger the emergence of degenerative diseases such as cardiovascular, atherosclerosis, and diabetes mellitus. Indonesian people's awareness of health has led to a trend of seeking for alternative food to prevent degenerative diseases. Functional drinks based on antioxidants from natural ingredients have become a potential solution to solve this issues. This study aims to determine the chemical characteristics and sensory quality of functional drinks in the form of instant tea bags made from pigeon pea, cinnamon, and lime peel. The parameters tested in this study were functional groups of organic compounds using FTIR, moisture content using the thermogravimetric method, pH value, sugar content using the Luff Schoorl method, antioxidant activity using the DPPH method, and organoleptic tests using the scoring method to assess the sensory quality of tea. The results showed that the highest moisture content was obtained in F4 at 8.56% and the lowest value in F1 at 6.97%. The highest pH value was in F4 with a value of 6.76 and the lowest in F5 at 5.72. Antioxidant compound analysis confirmed that all tea formulations has a very strong antioxidant capacity for all formulas with the highest IC50 value obtained in F1 at 1.29 ppm. In terms of total organoleptic score for color, aroma and flavor, the most preferred formula is F1> F2> F4> F5> F3 with scores respectively of 4.16; 4.17; 3.40; 3.28; and 3.07. Based on all the chemical and sensory characteristics of the antioxidant tea products, formulations F1and F2 have the potential to be further development.